PERANG JAMBI- JOHOR (1667 – 1679) SEBAGAI SEJARAH SOSIAL - Arif Rahim (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This paper discusses the War Jambi - Johor in the perspective of social history. The writing is driven by the desire to show the history of Jambi in perspective methodology that is separated from the conventional historical approach. Through a historical approach strukturis Jambi war-Johor occurring within the period 1667 - 1679 are examined using the concepts of the social structure, agency, social change, and the causal power. Thus it is known that the presence of waterway which structurally is an important international shipping lanes. The conflict between the two eventually progress to a series of open war. Jambi's defeat in the war in 1679 has resulted in social change in the empire From the perspective of social history, conflict Jambi - Johor caused by the desire of both parties to seize hegemony in the waterway. The struggle for hegemony driven Jambi. These changes include the loss of Jambi position as the main pepper port on the East Coast of Sumatra, which followed the weakening of the authority of the empire. Weak sultanate authority has changed the role of the Orang Laut from the imperial forces become pirates. The existence of pirates has caused reluctance trader upstream (Minangkabau) to trade in Jambi, and therefore contributes greatly to the income of the sultan. Johor action is blocking the arrival of Jambi daughter as a wife as a young king to come to Johor Johor and disconnect from marriage, is a causal factor of open warfare that have an impact on social changeKeyword : war Jambi-Johor